Uso de resumos gráficos baseados em mapas conceituais para apoiar a seleção de estudos primários no processo de revisão sistemática na engenharia de software - Takemiya, Stephane Hesae (2017)
Background: A Systematic Review (SR) aims to identify, evaluate and interpret available evidence on an specific research question or phenomenon of interest. One of the activities involved in conducting of SR is the primary studies selection, wich involves at first, the reading of abstracts studies. The execution of this activity tends to be difficult due to the large number of studies to be read and the bad abstract’s quality. Therefore, it is necessary to improve the abstracts quality in Software Engineering (SE). Objective: This work has two objectives: (i) to propose a generic model of graphical abstract based on concept maps (CM) as well as guidelines on how to elaborate it from the defined model; and (ii) to investigate whether the use of CMs based on graphical abstract could support the primary studies selection activity. Method: A exploratory study was conducted in order to compare the efficiency and effectiveness of PhD and master´s students in selecting studies using graphical abstracts which were elaborated using the proposed model. Results: Initial evidence showed that the average efficiency in selecting studies using textual and graphical abstracts was 23 and 20 minutes. The effectiveness was 13,75 studies using textual abstracts and 14,75 using graphical abstracts. The participants were more motivated to use graphical abstracts. Conclusion: These inicial evidences show that textual and graphical abstracts can assist the selection of primary studies, however the activity is less tedious using the graphical versions.